ANALYSIS OF SYNONYMOUS SIMILARITIES OF LEXICAL UNITS - Tulaboyeva, Gulorom (Журнал иностранных языков и лингвистики, 2023)
In the article, the author regards pairs of such vocabulary units, which are usually defined in lexicology as double forms, as absolute or complete synonyms. The main idea of ​​the publication is that by examining such lexical pairs they reveal such functional properties of their members that would allow abandoning the characterization of such units as absolutely identical doublets. Using the material of English nouns marked as absolute synonyms in specialist publications and dictionaries, we show that in many cases there is a differentiation of members of lexical pairs that takes them beyond the boundaries of doublet units. It turns out that due to the semantic and formal redundancy of such language forms, many absolute synonyms not only do not disintegrate in their function, as linguists predict but also exist for a long time without any perceived desire for transformation. There are factors (reasons) in the language that contribute to the functioning of absolute synonyms. The analysis shows that the set of doublet forms of existence-promoting factors is specific on the one hand for units with terminological characters and on the other hand for absolute synonyms with a common character.